2023
DOI: 10.3847/1538-4357/accf8d
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Modeling Polycyclic Aromatic Hydrocarbon Emission in Galaxy Evolution Simulations

Desika Narayanan,
J.-D. T. Smith,
Brandon S. Hensley
et al.

Abstract: We present a new methodology for simulating mid-infrared emission from polycyclic aromatic hydrocarbons (PAHs) in galaxy evolution simulations. To do this, we combine theoretical models of PAH emission features as they respond to varying interstellar radiation fields, grain-size distributions, and ionization states with a new model for dust evolution in galaxy simulations. We apply these models to three idealized arepo galaxy evolution simulations within the smuggle physics framework. We use these simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…We set a wide tolerance of q PAH due to the fact that the observed 24 μm is located at the redshifted PAH emission region so that the 24 μm is sensitive to the PAH emission strength. Recent results from simulations also suggest a wide range of q PAH (Narayanan et al 2023).…”
Section: Dust Emissionmentioning
confidence: 90%
“…We set a wide tolerance of q PAH due to the fact that the observed 24 μm is located at the redshifted PAH emission region so that the 24 μm is sensitive to the PAH emission strength. Recent results from simulations also suggest a wide range of q PAH (Narayanan et al 2023).…”
Section: Dust Emissionmentioning
confidence: 90%
“…Specifically, we do not model an evolving grain-size distribution in SIMBA, which could significantly change the thermodynamics of the ISM in these galaxies and drive changes in the ways dust absorbs and emits as a function of wavelength. It is known that dust of differing grain sizes have different optical properties and thus dominate galaxy spectra at different wavelengths; e.g., PAHs with grain sizes ∼1-10 Å dominate galaxy emission in the near-to mid-IR (e.g., Narayanan et al 2023). While we cannot test the impact of galaxy dust grain size distributions and how this manifests in IR SEDs, we predict that the addition of a self-consistent grain size evolution model, resulting in nonuniversal dust optical properties and perhaps a wider diversity in FIR SED shapes, would result in greater uncertainties in the inferred dust temperatures from modified blackbody fits to FIR SEDs.…”
Section: Caveats To Our Modelmentioning
confidence: 99%
“…Understanding the physics behind the enhanced durability of the smallest dust particles, which give rise to the excess emission from PAH 3.3 emitters, carries significant implications for simulating the dust mass buildup and chemical enrichment throughout cosmic time (e.g., Narayanan et al 2023). Theoretical studies have shown that molecules consisting of fewer carbon atoms (N c  40) are able to efficiently dissipate the absorbed UV energy via recurrent fluorescence (RF), with a relaxation timescale of ∼milliseconds as opposed to IR emission with timescales of ∼seconds (Leger et al 1988).…”
Section: The Excess Of Pah 33mentioning
confidence: 99%